Graphene-based materials do not impair physiology, gene expression and growth dynamics of the aeroterrestrial microalga Trebouxia gelatinosa. Issue 4 (21st April 2019) - Banchi, Elisa; Candotto Carniel, Fabio; Montagner, Alice; Bosi, Susanna; Bramini, Mattia; Crosera, Matteo; León, Verónica; Martín, Cristina; Pallavicini, Alberto; Vázquez, Ester; Prato, Maurizio; Tretiach, Mauro
Abstract: The effects of two graphene-based materials (GBMs), few-layers graphene (FLG) and graphene oxide (GO), were studied in the aeroterrestrial green microalga Trebouxia gelatinosa . Algae were subjected to short- and long-term exposure to GBMs at 0.01, 1 and 50 μg mL − 1 . GBMs internalization after short-term exposures was investigated with confocal microscopy, Raman spectroscopy and TEM. Potential negative effects of GBMs, compared to the oxidative stress induced by H2 O2, were verified by analyzing chlorophyl a fluorescence (Chl a F), expression of stress-related genes and membrane integrity. Effects of up to 4-week-long exposures were assessed analyzing growth dynamics, Chl a F and photosynthetic pigments. GBMs were not observed in cells but FLG was detected at the interface between the cell wall and plasma membrane, whereas GO was observed adherent to the external wall surface. FLG caused the down-regulation of the HSP70-1 gene, with the protein levels remaining stable, whereas GO had no effect. In comparison, H2 O2 produced dose- and time-dependent effects on Chl a F, gene expression and HSP70 protein level. Long-term exposures to GBMs did not affect growth dynamics, Chl a F or photosynthetic pigment contents, indicating that the few observed short-term effects were not dangerous on the long-term. Results suggest that interactions between FLG and plasma membrane were harmless, activating a down-regulation of the HSP70-1 gene similar to that induced by H2 O2 . Our work shows that studying GBMs effects on non-model organisms is important since the results of model green microalgae are not representative of the whole taxonomic group.